Developing an Empirical Relationship to Predict the Wear Characteristics of Ni-Based Hardfaced Deposits on Nuclear Grade 316LN Austenitic Stainless Steel. (14th October 2021) - Gnanasekaran, S.; Chelladurai, Samson Jerold Samuel; Padmanaban, G.; Arthanari, Ramesh; Balasubramanian, V.
Abstract : Using the nickel-based Colmonoy 5 hardfacing alloy, components made of austenitic stainless steel (ASS) used in nuclear power plants can be hardfaced. Hardfacing is the process of applying complex and wear-resistant materials to substrates that require abrasion resistance. The tribological characteristics of a reactor-grade material NiCr-B hardfaced deposit were studied and reported in this paper. Hence, in this investigation, an effort has been made to develop empirical relationship to predict weight loss of laser hardfaced Ni-based alloy surface incorporating laser parameters using statistical tools such as design of experiments (DoE) and analysis of variance (ANOVA). The developed empirical relationship can be effectively used to trail the weight loss (wear resistance) of laser hardfaced nickel alloy surfaces by altering laser parameters. This method has proven very effective. A power of 1300 W, powder feed rate of 9 g/min, travel speed of 350 mm/min, and defocusing distance of 32 mm were all combined to achieve a minimum weight loss of 0.0164 grams.